The synthesis methods of the system structure of the information and analytical supporting of National guard of Ukraine grouping in cases of emergency - Drobakha, H. A.; Kovaliov, І. V.; Bashkatov, Ye. H.; Petik, А. V.; Shapoval, О. М. (Honor and Law, 2019)
The synthesis method of the system structure of the, necessary for the information and analytical supporting of National guard of Ukraine grouping are considered. The approaches for the rational determination of the system structure of the information and analytical supporting are offered.